An effectiveness factor model for slurry phase olefin polymerizations. (6th April 2022) - Zhang, Shuaifeng; Zhang, Qinghua; Kong, Bo; Yang, Chao; Fox, Rodney O.
Highlights: An effectiveness factor model (EFM) is developed from MGM for slurry polyolefin reactions. The concentration gradient inside macroparticles is modeled by an effectiveness factor. The effect of catalyst characteristics and temperature on the growth of macro- and micro- particles are investigated. The EFM can produce similar results as the MGM with a much lower computation cost when αi, mp < 2.0. Abstract: The multigrain model (MGM) is the most widely used single-particle model, giving a detailed description of phenomena during olefin polymerization. However, the detailed modeling of the diffusion–reaction process inside the catalyst particles requires solving a large number of ordinary differential equations, which is unsuitable for coupling with multiphase CFD tools. That is the reason why the current CFD simulation studies of olefin polymerization reactors rarely consider intraparticle transport. To fill this gap, an effectiveness factor model (EFM) is developed from MGM for slurry olefin polymerizations. It maintains the multilevel framework of MGM and is suitable for use in multiphase CFD simulations. The MGM and EFM are first implemented into OpenFOAM. Moreover, the EFM has been validated by comparison with literature data. Detailed comparisons between MGM and EFM show that the EFM can produce similar results as the MGM with a much lower computation cost for olefin slurry polymerization when αi, mp < 2.0.